Case study of successful senior citizen employment in Japan introduction of “woe” and “ase” business model - Iwao Kato; Fumitaka, Furuoka; Lim, Beatrice; Khairul Hanim Pazim; Balakrishnan Parasuraman; Balan Rathakrishnan (Researchers World, 2010)
This paper reviews the recent progress of Japan’s senior citizen employment and undertakes a case study of one successful senior citizen employment that a company in Gifu prefecture Japan began eight years ago. In 2001, “Kato Sangyo”, one small company in Gifu prefecture, began the employment of over 60 years-old senior citizens. The company employed 15 senior citizens at first. The oldest woman employed by the company was 79 years old at that time. She is still now working for the company. At present, 40 workers out of total 96 employees in the company are over 60 years old. Regarding this challenging employment trial, many mass media including Wall Street Journal have already reported. The article of Wall Street Journal introduced the senior citizen employment of Kato Sangyo as one of the most successful employment model in Japan, and it took up Kato Sangyo as a symbol of Japan's recent changing employment circumstances. In addition, this paper provides a result of the recent interview to CEO of Kato Sangyo, and the questionnaire survey of the senior citizen workers of the company. This case study could be useful for the researchers who are interested in the senior citizen employment or the connected field.